Study on the water vapor adsorption Characteristics of Carbon materials in HTGR. Issue 1 (May 2021) - KaiYue, Shen; Da, Yan; HuaQiang, Yin; XueDong, He; Tao, Ma; hua, Fan
Abstract: High-temperature gas-cooled reactor (HTGR) is the first kind of power plant with fourth-generation features in the world, and a large amount of graphite and carbon material is adopted as structural material and fuel matrix material, including boron-containing carbon (BC) and isostatic pressure graphite (IG-110). As a kind of porous material, the carbon material contains a certain amount of moisture, which will impose negative effects on reactor safety. Therefore, this paper studies the water vapor adsorption characteristics of carbon materials in HTGR. The adsorption isotherms of BC and IG-110 were obtained by experimental measurements. Experiments show that the moisture adsorption of IG-110 is much lower than that of BC at various relative humidity. The experimental data is analysed by the BET, GAB, DA, Oswin adsorption models.